Multiple thermal fronts near the Patagonian shelf break - Franco, B.C. (2008)
Eighteen year (1985-2002) sea surface temperature (SST) data are used to study the intraseasonal variability of the Patagonian shelf break front (SBF) in the SW South Atlantic Ocean between 39° and 44°S. The cross-shelf break SST gradients reveal distinct, previously undocumented thermal fronts located both, offshore and inshore of the SBF. Throughout the year the main SBF, identified as a band of negative SST gradient maxima (relatively strong offshore temperature decrease), forms a persistent feature located closed to the 200 m isobath, while two distinct negative gradient maxima are located inshore and offshore of this location. Daily SST images reveal the presence of three branches of cold waters whose edges delineate the above mentioned fronts. The two offshore branches closely follow lines of constant potential vorticity (f/h) and appear to be associated with the Malvinas Current, while a third branch, located further onshore, is not steered by the bottom topography. South of 40°S the onshore branch forms a quasi permanent front parallel to the SBF. Copyright 2008 by the American Geophysical Union.